Prevalence of arps10, fd, pfmdr-2, pfcrt and pfkelch13 gene mutations in Plasmodium falciparum parasite population in Uganda - Ocan, Moses; Katabazi Ashaba, Fred; Mwesigwa, Savannah; Edgar, Kigozi; Kamya, Moses R.; Nsobya, Sam L. (Plos one, 2022)
In Uganda, Artemether-Lumefantrine and Artesunate are recommended for uncomplicated and severe malaria respectively, but are currently threatened by parasite resistance. Genetic and epigenetic factors play a role in predisposing Plasmodium falciparum parasites to acquiring Pfkelch13 (K13) mutations associated with delayed artemisinin parasite clearance as reported in Southeast Asia. In this study, we report on the prevalence of mutations in the K13, pfmdr-2 (P. falciparum multidrug resistance protein 2), fd (ferredoxin), pfcrt (P. falciparum chloroquine resistance transporter), and arps10 (apicoplast ribosomal protein S10) genes in Plasmodium falciparum parasites prior to (2005) and after (2013) introduction of artemisinin combination therapies for malaria treatment in Uganda. A total of 200 P. falciparum parasite DNA samples were screened. Parasite DNA was extracted using QIAamp DNA mini kit (Qiagen, GmbH, Germany) procedure. The PCR products were sequenced using Sanger dideoxy sequencing method. Of the 200 P. falciparum DNA samples screened, sequencing for mutations in K13, pfmdr-2, fd, pfcrt, arps10 genes was successful in 142, 186, 141, 128 and 74 samples respectively. Overall, we detected six (4.2%, 6/142; 95%CI: 1.4–7.0) K13 single nucleotide polymorphisms (SNPs), of which 3.9% (2/51), 4.4% (4/91) occurred in 2005 and 2013 samples respectively. All four K13 SNPs in 2013 samples were non-synonymous (A578S, E596V, S600C and E643K) while of the two SNPs in 2005 samples, one (Y588N) is non-synonymous and the other (I587I) is synonymous. There was no statistically significant difference in the prevalence of K13 (p = 0.112) SNPs in the samples collected in 2005 and 2013. The overall prevalence of SNPs in pfmdr-2 gene was 39.8% (74/186, 95%CI: 25.1–50.4). Of this, 4.2% (4/95), 76.9% (70/91) occurred in 2005 and 2013 samples respectively. In 2005 samples only one SNP, Y423F (4.2%, 4/95) was found while in 2013, Y423F (38.5%, 35/91) and I492V (38.5%, 35/91) SNPs in the pfmdr-2 gene were found. There was a statistically significant difference in the prevalence of pfmdr-2 SNPs in the samples collected in 2005 and 2013 (p<0.001). The overall prevalence of arps10 mutations was 2.7% (2/72, 95%CI: 0.3–4.2). Two mutations, V127M (4.5%: 1/22) and D128H (4.5%: 1/22) in the arps10 gene were each found in P. falciparum parasite samples collected in 2013. There was no statistically significant difference in the prevalence of arps10 SNPs in the samples collected in 2005 and 2013 (p = 0.238). There were more pfmdr-2 SNPs in P. falciparum parasites collected after introduction of Artemisinin combination therapies in malaria treatment. This is an indicator of the need for continuous surveillance to monitor emergence of molecular markers of artemisinin resistance and its potential drivers in malaria affected regions globally
Keywords: Arps10; pfmdr-2; Gene mutations; Plasmodium falciparum